Exploring the Role of Optimism in Shaping Subjective Well-Being among Tahfidz Students - Zahara, Cut Ita; Fera Rahmayani; Nur Afni Safarina (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
This study aims to examine the relationship between optimism and subjective well-being among Tahfidz Islamic boarding school students. Students in Tahfidz schools face unique academic and spiritual demands that may influence their psychological well-being. Using a quantitative correlational research design, data were collected from 165 students selected through quota sampling. The research instruments included the Subjective Well-Being Scale by Aliya (2020) and the Optimism Scale by Asfia (2017). Data analysis employed Pearson’s Product-Moment Correlation using SPSS 26.0. The results revealed a significant positive relationship between optimism and subjective well-being (r = 0.367, p < 0.05), indicating that higher optimism corresponds to higher well-being among Tahfidz students. Among the optimism aspects, permanence showed the strongest correlation with well-being. These findings highlight the importance of fostering optimism to enhance students’ emotional resilience and life satisfaction within Islamic boarding school settings.